Causal associations between type 2 diabetes mellitus, glycemic traits, dietary habits and the risk of pressure ulcers: univariable, bidirectional and multivariable Mendelian randomization - Luo, Pei; Huang, Can (Frontiers in Nutrition, 2024)
Objective: Previous research has established a connection between Type 2 Diabetes Mellitus (T2DM), glycemic traits, dietary habits, and the risk of Pressure Ulcers (PUs). The aim of our study is to disentangle any potential causal relationship between T2DM, glycemic traits, and dietary factors, and the risk of PUs.The exposure and outcome datasets were sourced from the IEU Open GWAS project, the Meta-Analyses of Glucose and Insulin-related traits Consortium (MAGIC), and the FinnGen biobank, respectively. The primary MR analysis method employed was the inverse variance-weighted method. Furthermore, we employed multivariable MR (MVMR) adjusting for BMI. Then, we investigated the possibility of a reverse association between glycemic traits and PUs through bidirectional MR. Finally, Heterogeneity and pleiotropic analysis were conducted to ensure the accuracy and robustness of the results.The findings revealed that T2DM (OR = 1.282, 95% CI: 1.138 -1.445, p < 0.001) and Fasting Glucose (FG; OR = 2.111, 95% CI: 1.080 -4.129, p = 0.029) were associated with an increased risk of PUs, while salad/raw vegetable intake (OR: 0.014; 95% CI: 0.001 -0.278; p = 0.005) was identified as a protective element. However, no other dietary elements demonstrated a statistically significant causality with PUs. In addition, in the reverse direction, there were positive correlation between genetic susceptibility to PUs and an increase in FG (OR: 1.007, 95% CI: 1.000 -1.013, p = 0.048) and Fasting Insulin (FI; OR: 1.012, 95% CI: 1.003 -1.022, p = 0.011). MVMR results indicated that the causal effect of T2DM on PUs was independent of BMI (OR: 1.260, 95% CI: 1.112 -1.427, p < 0.001). These results remained robust when considering weak instrument bias, pleiotropy, and heterogeneity.This study establishes a causal link between genetically predicted T2DM， FG and an increased risk of PUs. Conversely, Salad/raw vegetable intake is significantly inversely associated with PUs. Simultaneously, we identified two downstream effector factor (FG and FI) that were associated with PUs. These findings may have clinical implications for both prevention and treatment.